2016
DOI: 10.14260/jemds/2016/632
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Lipid Profile in Patients With Pancreatitis

Abstract: Pancreatitis is one of the most frequent gastrointestinal tract disease for hospitalization all over the world, leading to tremendous emotional, physical and financial human burden. The spectrum of aetiological factors for pancreatitis varies according to continents. Hyperlipidaemia is a rare but known and established risk factor for pancreatitis and goes undetected in most of the clinical settings. Early diagnosis of hyperlipidaemia induced pancreatitis is important to prevent its recurrence and complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…it's also liable for cholesterol homeostasis by transporting excessive cholesterol from tissue to the liver andmore emphasis placed upon its anti-inflammatory effect. 17 In our study, we found that increased TC Level and decreased HDL-C within the disease control group compared with the control group. Ginger extract (200 mg/kg and 400 mg/kg) both doses are reduced TC and increased 'GOOD CHOLESTEROL' (HDL-C) but it doesn't have a big effect on LDL-C level.…”
Section: Estimation Of Hdl Cholesterol (Hdl-c) Andldl Cholesterol (Ldl-c)supporting
confidence: 49%
See 1 more Smart Citation
“…it's also liable for cholesterol homeostasis by transporting excessive cholesterol from tissue to the liver andmore emphasis placed upon its anti-inflammatory effect. 17 In our study, we found that increased TC Level and decreased HDL-C within the disease control group compared with the control group. Ginger extract (200 mg/kg and 400 mg/kg) both doses are reduced TC and increased 'GOOD CHOLESTEROL' (HDL-C) but it doesn't have a big effect on LDL-C level.…”
Section: Estimation Of Hdl Cholesterol (Hdl-c) Andldl Cholesterol (Ldl-c)supporting
confidence: 49%
“…The parameters of lipid profilenamelyTC, LDL-C, are higher and HDL-C is lower in pancreatitis. 17 The protein composition of HDL Apolipoprotein A1 (APO-A1) depleted which is that the major protein component of HDL. it's also liable for cholesterol homeostasis by transporting excessive cholesterol from tissue to the liver andmore emphasis placed upon its anti-inflammatory effect.…”
Section: Estimation Of Hdl Cholesterol (Hdl-c) Andldl Cholesterol (Ldl-c)mentioning
confidence: 99%